Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-74000-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual Communication Support Using the Language Grid

Abstract: Abstract. Our proposed "Language Grid" infrastructure supports multilingual communication by combining in new way language resources, such as machine translators, morphological analyzers, and dictionaries specific to user communities. We developed the Language Grid as a language infrastructure on the Internet. The Language Grid enables user communities to combine two or more machine translators and their community dictionaries by workflows, and to easily create new multilingual services specific to the communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This means advances in methods and algorithms are not always available to individuals relying on free Internet based tools. Consequently there are issues with the quality of MT which may require a level of post-editing to correct the raw output so that it is fit for purpose (Inaba et al 2007). …”
Section: Online Writing Toolsmentioning
confidence: 99%
“…This means advances in methods and algorithms are not always available to individuals relying on free Internet based tools. Consequently there are issues with the quality of MT which may require a level of post-editing to correct the raw output so that it is fit for purpose (Inaba et al 2007). …”
Section: Online Writing Toolsmentioning
confidence: 99%
“…It enables better understanding of online content written in different languages by people from different countries. Inaba et al tested the usability of thier multilingual communication systems using the Language Grid [5]. They found the root cause of the translation errors and suggested that the use of community dictionaries could possibly improve the translation results.…”
Section: A Multilingual Communication Supportmentioning
confidence: 97%
“…On a scale of "very good," "good," "not bad," and "bad," translations from Japanese to Chinese, Japanese to Korean, and Korean to Japanese were reported as "good," and Chinese to Japanese translations were labeled "not bad" in one study (Ogura, et al, 2004). Other accuracy results were merely anecdotal, e.g., "although there were many mistakes in the grammar of the translated French, it was still possible to catch the meaning from the context of what was being said" (Inaba, et al, 2007) and "although most of the students were satisfied with the software, some students wanted more accuracy and user friendliness" (Sakai, et al, 2008).…”
Section: Multilingual Meeting Systemsmentioning
confidence: 99%